Russia in the Arctic ... : development plans, military potential, and conflict prevention ... - Paul, Michael; Swistek, Göran (Stiftung Wissenschaft und Politik (SWP), German Institute for International and Security Affairs, 2022)
SWP Research Paper, 3/2022 ...